PENDIDIKAN MULTIKULTURALISME DI ERA MODERN (Dialektika Kritis Pendidikan Islam Monokotomik) - jasmani, Jasmani (LP2M IAIN Palangka Raya, 2012)
Monokotomic education is the educational system construction of the plenary which is capable of integration educational value of domain-oriented humanitarian and religious by a nature.The education system also implies an attitude of valuing differences in values, norms, culture and tradition (Multiculturalism) as well as of the religious aspect of pluralism as a consequence of the Muslims. Therefore, there needs to be a paradigm in education it is necessary to elaborate on the elements of cultural pluriformity become construction between the wisdom or community â read the culture. It is intended as an attempt to construct a more civilized society structure, harmonious, and prosperous with cache while respecting cultural differences. Konstruks education is believed to be supporting the formation of communities of multiculturalism and pluralism in this modern era; where the whole community with all the elemental sued for bears fate and interdependence together for the creation of a lasting peace. Therefore, education (Islamic) multiculturalism with the paradigm of monokotomic need to be constructed which will later put forward positional egalitarian culture system at all, so its able to eliminate the superiority-inferiority between one culture and other cultures. Where he will give a positive effect against civic buildings marked with the behavior or attitude of mutual respect and respect the differences, open minded, and mutual understanding as well as giving understanding among community members.Â Abstrak:Â Pendidikan monokotomik merupakan konstruksi sistem pendidikan paripurna yang mampu mengintegralisasikan nilai pendidikan yang berorientasi pada domain kemanusiaan dan kealaman dengan keagamaan. Sistem pendidikan demikian berimplikasi pada suatu sikap menghargai perbedaan tata nilai, norma, budaya dan tradisi (multikulturalisme) termasuk juga dari aspek agama sebagai konsekuensi dari pandangan pluralisme umat Islam. Oleh sebab itu, paradigma yang perlu ada dalam pendidikan perlu untuk mengelaborasi elemen-elemen kemajemukan budaya menjadi konstruksi kearifan antar golongan atau komunitas âbaca budaya. Hal ini dimaksudkan sebagai upaya untuk membangun struktur masyarakat yang lebih beradab, harmonis, dan sejahtera dengan tetap menghargai khazanah perbedaan budaya. Konstruks pendidikan ini yang diyakini akan menyokong terbentuknya masyarakat multikulturalisme dan pluralisme di era modern ini; di mana seluruh masyarakat dengan segala unsurnya dituntut untuk saling tergantung dan menanggung nasib secara bersama-sama demi terciptanya perdamaian abadi. Oleh sebab itu, pendidikan (Islam) multikulturalisme dengan paradigma monokotomik perlu untuk dikonstruksi yang nanti akan mengedepankan posisional egaliter pada semua sistem kebudayaan, sehingga mampu menghilangkan superioritas-inferioritas antara satu kebudayaan dengan kebudayaan lainnya. Di mana ia akan memberikan efek positif terhadap bangunan kemasyarakatan yang ditandai dengan perilaku atau sikap saling menghargai dan menghormati dalam perbedaan, open minded, dan saling memahami serta memberi pengertian antar anggota masyarakat.